sleuth or dare / Framed & Dangerous - Harrington, Kim (New York Scholastic, 2012)
Happily accepting a case from her crush Zane, who has been wrongly accused of stealing money from the school store, Norah and her best friend, Darcy, resolve to prove his innocence in spite of the principal's opinions.
K
580
K